IMPACT OF VIRTUAL LABORATORIES ON SCIENCE PROCESS SKILLS AND INTEREST IN LEARNING SCIENCE AMONG PRIMARY SCHOOL STUDENTS - Fitri, Ummiatul; Putri, Aissy; Fitria, Yanti; Kharisma, Inggria (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This paper seeks to investigate the effectiveness of virtual laboratory in enhancing elementary school pupils’ scientific process skills and interests in the learning of science. A quantitative approach employing a quasi-experimental design was adopted including two groups of pupils i.e. a group that utilized virtual laboratories and a group that was taught using the traditional methods. The research instruments comprised of the science process skills pretests, which were administered prior to the intervention, and science process skills post tests, which were administered after the intervention together with questionnaires that measured students’ interest in the learning of science before and after the intervention. Data analysis was performed using percentage frequency, means and standard deviations, single factor ANOVA testing for homogeneity, independent t-tests and N-Gain to evaluate the level of effectiveness of the intervention. The findings highlight that the experimental group gained significantly more than the control group. The experimental group that employed the use of virtual laboratories had a higher mean posttest score of 0.67 indicating a high Ngain and thus higher science process skills acquisition. However the control group only showed a N-Gain of 0.20. Further, the analysis of the questionnaires showed an even greater gain in learning interest of members of the experimental group indicating that virtual laboratories enhance the acquisition of higher order skills through more active learning approaches. Research of this type suggests that technology-based media especially virtual laboratories can serve as an alternative for the improvement of student learning outcomes and interest in science education. Hence, the use of virtual laboratories can be seen as an innovative pedagogical approach that helps to increase target outcomes of 21st century education in science, in particular